(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article is devoted to the peculiarities of the organization of physical-mathematical training in US maritime higher education institutions. The author draws attention to the fact that one of the actual vectors of pedagogical research is the study of international experience in organizing education and training of specialists for various sectors of the world economy. Analysis of scientific sources made it possible to determine that the problem of physical-mathematical training in foreign maritime higher educational institutions was not the subject of a separate research in modern pedagogical thought. The purpose of the article is to study the characteristics of the organization of physical-mathematical training in US maritime higher educational institutions and to determine the possibility of using their positive experience in the domestic maritime educational system. In the article the author analysis and compares curriculums of some US maritime academies. During the analysis, it was finding that physical-mathematical training plays a special role in the US system of maritime professional education. It provides not only the development of basic knowledge of physics, mathematics, astronomy and computer science but also aims to develop the basic skills and abilities of students necessary for further education and professional activity. Among them, the departments of science and mathematics of US maritime academies focus on the development of quantitative and qualitative thinking of students, their use of experimental and statistical methods, determining causal relationships, finding solutions to professional tasks, forecasting and modeling, forming a students’ worldview through mastering fundamental scientific principles, etc. The author comes to the conclusion that the experience of organizing physical-mathematical training in US maritime academies can be used by the domestic maritime educational system during the planning of the variable component of professional training programs for the maritime industry.